KAJIAN POTENSI LAHAN RAWA UNTUK PENGEMBANGAN PERKEBUNAN KELAPA SAWIT KABUPATEN HULU SUNGAI TENGAH KALIMANTAN SELATAN - Ahmad Baparki; Yayuk Minta Wahyuningsih (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2019)
Hulu Sungai Tengah District has Wetlands in the Form of a Swamp of Shallow Valleys,Mid Valley and the Valleys in Total Area of 16-20 Thousand Hectares. The Potential Swamp Area in the Study Area Reached 21.318 Hectares With Details of the Shallow Swamp Typology of 4.227 Hectares , a Rare Fall of 15.934 Hectares and 1.157 Ha of Rain Fed. The implementation of This Study Includes Reference Studies, Field Activities,Laboratory Analysis and Data Processing,Map Making and Report Preparation. The Most Extensive Potential of Land in The Northern Sub District of 10.875 Ha With the Middle Rare Typology.Based on the Typology of the Study Area,it Consists of Potential Land Area of 14.685 Ha and Peatland Area of 6.633 Ha.The Results of The Overall Evaluation of Land From 21.318 Ha Were Planted For Plantations of 12.557 Ha and 4.461 Ha For Conservation and 4.300 Ha of Enclaves.Land Suitability Distribution From 12.557 Ha if Reduced Area of 5.005 Ha Wide Area Effective 7.550 Ha.The Public”s Views on Plantations Are Still Diverse,Some of Which View Positively 15.55 %,Negative 21.6 % and Neutral 63.34 %. A Positive View Means the Respondent agrees to the Existence of a Plantation Because it is Considered to Provide Hope of Getting Employment Opportunities or Income that Can Provide a Better Guaranteee Than The Present Situation.